Effect of the energy content of diets on the development and quality of the fat reserves of larvae and reproduction of adults of the black soldier fly, Hermetia illucens (Diptera: Stratiomyidae) - Bogdan GEORGESCU (Institute of Entomology, Biology Centre, Czech Academy of Science, 2021)
Hermetia illucens is a sustainable and an increasingly bioeconomical source of nutrients for farm animals. It is still necessary, however, to improve our knowledge of the biological features of this species in order to maximize its use. The aims of this research were to evaluate the effect of the energy level of rearing diets on its body weight and fat-body reserves. The quantity and quality of the fats storred by the non-feeding stages of this insect and its reproductive performances were also studied. A control diet (CD - Gainesville diet) and three diets with progressively greater energy contents (kcal/kg ME) were formulated. The increase was achieved by including different amounts of maize, 40% (ED1), 60% (ED2) and 80% (ED3), in these three diets. Abother diet (ED4) consisted of fruit and vegetable waste. The results indicate that the body weight of larvae, prepupae, pupae and adult flies, as well as fat content of the larvae increased significantly (p ˂ 0.01) with increase in the energy content of the diets. There was a positive Pearson correlation between energy content of diets and body weight of adult flies. The heaviest egg clutches with the highest number of eggs/clutch (p ˂ 0.01) were laid by flies reared on the diets with the highest energy content. The quality of the fat stored by larvae did not influence the weight and number of egg laid.